Management of Diabetic Ketoacidosis in Patient with HeartFailure - Febrianto, Dicky; Hindariati, Est (Jurnal Penyakit Dalam Indonesia, 2021)
Diabetic ketoacidosis (DKA) is diabetes mellitus emergency which is defined by the biochemical triad of hyperglycemia, ketonemia, and acidemia. Diabetic ketoacidosis continues to have high rates of morbidity and mortality despite advances in the treatment of diabetes. Crucial aspects of DKA management involve adequate replacement of fluids and electrolytes, particularly potassium, and the continuous administration of insulin. Hydration status in patients with DKA and heart failure can be assessed by physical examination, such as consciousness, vital signs, capillary refill time, skin turgor, jugular venous pressure, and signs of pulmonary edema. Invasive and non-invasive methods can also assess fluid adequacy in rehydration of patients with DKA and heart failure. Invasive methods include central venous pressure (CVP) and pulmonary artery pressure, while non-invasive methods include echocardiography, bioimpedance vector analysis (BIVA), and brain natriuretic peptide (BNP). By assessing hemodinamic status properly in an intensive care setting, a patient with heart failure who develops DKA can be administered adequate quantities of fluid to avoid dehydration or overhydration.